Calcium electroporation for treatment of cutaneous metastases; a randomized double-blinded phase II study, comparing the effect of calcium electroporation with electrochemotherapy. (4th March 2018) - Falk, H.; Matthiessen, L.W.; Wooler, G.; Gehl, J.
Abstract: Background: Calcium electroporation is a novel anticancer treatment, which utilizes high voltage pulses to permeabilize cell membranes and expose the cell to supraphysiological doses of calcium. Preclinical studies on calcium electroporation have shown strikingly high tumor response with cell necrosis. Calcium electroporation builds on the treatment electrochemotherapy, where chemotherapeutic drugs, mostly bleomycin, are internalized by electroporation. This double-blinded randomized study compared calcium electroporation to electrochemotherapy in terms of objective response measured 6 months after treatment. Methods: Seven patients with a total of 47 cutaneous metastases from breast cancer and malignant melanoma were included in the protocol. A total of 37 metastases were randomized and evaluated for response, another 10 metastases were used for biopsy. This was a non-inferiority trial and metastases were randomized individually in each patient to either intratumoral calcium or bleomycin followed by application of electric pulses to tumor site. All metastases were treated once, and after 6-months of follow-up, the randomization code was revealed. Results: Objective response of calcium electroporation was 72% (13/18) with complete response in 66% (12/18). For electrochemotherapy, objective response was 84% (16/19) with complete response in 68% (13/19). There was no statistically significant difference between the two treatments ( p  = 0.5). After 1 year, only three out of 25 metastases had relapsed. Ulceration, itching and exudation were reported slightly more frequently in metastases treated with bleomycin, and hyperpigmentation was only seen in metastases treated with bleomycin. Conclusion: This study shows that calcium electroporation is feasible and effective in patients with cutaneous metastases.